Multiple Informant Agreement on the Anxiety Disorders Interview Schedule in Youth with Autism Spectrum Disorders - Storch, Eric A. (Mary Ann Liebert, Inc., 2012)
OBJECTIVE: The purpose of this study was to examine child, parent, and clinician's consensus agreement on the Anxiety Disorders Interview Schedule, Child and Parent versions (ADIS-C/P) in a sample of children and adolescents with autism spectrum disorders (ASD). METHOD: Youth with ASD (n=85; age range=7–17 years) and their parents were each administered the ADIS-C/P by a trained clinician. Consensus diagnoses were determined in a clinical conference using best estimate procedures that incorporated all available information. RESULTS: Children and youth with ASD diagnoses generally showed poor diagnostic agreement with parents and clinical consensus, whereas parents showed good-to-excellent diagnostic agreement with clinical consensus diagnoses. Diagnostic agreement between parents and consensus was moderated by the specific ASD diagnosis. Otherwise, the pattern of relationships did not systematically differ as a function of age or externalizing comorbidity. CONCLUSIONS: These data suggest that parent and youth agreement regarding the presence of clinical levels of anxiety is markedly poor among youth with ASD. Additionally, clinicians are likely to base their diagnostic impressions on parent report, placing minimal emphasis on child report.